The Effect of Magnetic Induction Spectroscopy Signal for Cylindrical Screw with Different Length - Amran, M.; Daud, R.; Zakaria, Z.; M.K. Ali Hassan, M.; I. Omar, M.; Mat, F. (International Journal of Engineering and Technology, 2018)
In medical surgical procedures, screw is commonly used when it comes into internal and external fixation surgery. The size of screw, which is classified as the diameter and length of screw plays an important role to stability the bone implant fixation. Previous studies showed there is lack of investigation on screw loosening detection that brings the problem of detecting the failures of bone implant in a long bone such as femur. Detection technique of this kind of problem is important in medical technologies to ensure better healing. The purpose of this study is to investigate the received signal of electromagnetic field on the different cylinder length by employing a single channel of magnetic induction spectroscopy. This study is used to evaluate the current density distribution in the cylinder screws under the action of electromagnetic field. The diameter of cylinder screw used in this simulation study is 3mm diameter based on the medical surgery procedures and the length of cylinder focuses onto 3 different lengths (22mm, 26mm, and 30mm). The simulation of this study concludes that COMSOL Multiphysic 5.2a software with a range of frequency 1MHz to 10MHz is used. The received magnetic field and current density of each model shows that the conductivity is changed based on the geometry of the cylindrical screw.Â Â